Is saving lives your task or God’s? Religiosity, belief in god, and moral judgment - Netta Barak-Corren; Max H. Bazerman (Judgment and Decision Making, 2017)
Should a Catholic hospital abort a life-threatening pregnancy or let a pregnant woman die? Should a religious employer allow his employees access to contraceptives or break with healthcare legislation? People and organizations of faith often face moral decisions that have significant consequences. Research in psychology found that religion is typically associated with deontological judgment. Yet deontology consists of many principles, which may, at times, conflict. In three studies, we design a conflict between moral principles and find that the relationship between moral judgment and religiosity is more nuanced than currently assumed. Studies 1 and 2 show that, while religious U.S. Christians and Israeli Jews are more likely to form deontological judgments, they divide between the deontological principles of inaction and indirectness. Using textual analysis, we reveal that specific beliefs regarding divine responsibility and human responsibility distinguish inaction from indirectness deontologists. Study 3 exploits natural differences in religious saliency across days of the week to provide causal evidence that religion raises deontological tendencies on Sundays and selectively increases the appeal of inaction deontology for those who believe in an interventionist and responsible God.